Association of Long-Term Risk Factor Levels With Carotid Atherosclerosis: The Chicago Healthy Aging Magnetic Resonance Imaging Plaque Study (CHAMPS). (September 2019) - Berry, Jarett D.; Mehta, Anurag; Lin, Kai; Ayers, Colby R.; Carroll, Timothy; Pandey, Ambarish; Garside, Daniel B.; Daviglus, Martha L.; Yuan, Chun; Lloyd-Jones, Donald M.
Abstract : Background: Absence of cardiovascular risk factors (RF) in young adulthood is associated with a lower risk for cardiovascular disease. However, it is unclear if low RF burden in young adulthood decreases the quantitative burden and qualitative features of atherosclerosis. Methods: Multi-contrast carotid magnetic resonance imaging was performed on 440 Chicago Healthy Aging Study participants in 2009 to 2011, whose RF (total cholesterol, blood pressure, diabetes mellitus, and smoking) were measured in 1967 to 1973. Participants were divided into 4 groups: low-risk (with total cholesterol <200 mg/dL and no treatment, blood pressure <120/80 mm Hg and no treatment, no smoking, and no diabetes mellitus), 0 high RF but some RF unfavorable (≥1 RF above low-risk threshold but below high-risk threshold), 1 high RF (total cholesterol ≥240 mg/dL or treated, blood pressure ≥140/90 or treated, diabetes mellitus, or smoking), and 2 or more high RF. Association of baseline RF status with carotid atherosclerosis (overall mean carotid wall thickness and lipid-rich necrotic core) at follow-up was assessed. Results: Among 424 participants with evaluable carotid magnetic resonance images, the mean age was 32 years at baseline and 73 years at follow-up; 67% were male, 86% white, and 36% were low-risk at baseline. Two or more high RF status was associated with higher carotid wall thickness (0.99±0.11 mm) and lipid-rich necrotic core prevalence (30%), as compared with low-risk group (0.94±0.09 mm and 17%, respectively). Each increment in baseline RF status was associated with higher carotid wall thickness (β-coefficient, 0.015; 95% CI, 0.004–0.026) and with higher lipid-rich necrotic core prevalence at older age (odds ratio, 1.26; 95% CI, 1.00–1.58) in models adjusted for baseline RF and demographics. Conclusions: RF status in young adulthood is associated with the burden and quality of carotid atherosclerosis in older age suggesting that the decades-long protective effect of low-risk status might be mediated through a lower burden of quantitative and qualitative features of atherosclerotic plaque. Abstract : Supplemental Digital Content is available in the text.